PROBLEMS IN TRANSLATING GERUND AND ITS COMPONENTS INTO VARIOUS LINGUISTIC SYSTEMS (Proceedings of International Educators Conference, 2023)
This article discusses the translation of the gerund and its parts into two different linguistic systems, namely Russian and Uzbek. By including factual examples, it resolves issues with the translation of sentences into various contexts.